E40: Implications for Financial Reporting - LEE, Peter (Institutional Knowledge at Singapore Management University, 1994)
E40 is a major accounting pronouncement, which will have significant impact on the financial community worldwide, including Singapore. The attempt by the international accounting community to set standards for the recognition, measurement and disclosure of financial instruments is a laudable endeavour. E40 includes several provisions that are departures from the traditional historical-cost and transaction-based accounting system. These include the use of fair values for the measurement of financial instruments, the recognition in the balance sheet of partially or wholly unperformed contracts, and the use of present value and option pricing models in measuring some financial assets and liabilities. In addressing issues that are central to the accounting for new financial instruments, E40 provides several challenges to the accounting profession. The profession can no longer rely on the historical-cost framework solely as a basis for measurement. In measuring new financial instruments accountants will be expected to have a sound knowledge of contemporary finance theory and measurement methods employed in finance. E40 must eventually be reconciled with the rest of the accounting framework.